The effects of strategic orientation patterns on marketing performance - an applied study in the Coca-Cola Soft Drinks Company/Babylon Branch - مؤمل حسين جويسم (Iraqi Journal for Administrative Sciences, 2024)
This study aims at identifying the effect of strategic directives (proactive, defensive, creative) on the dimensions of marketing performance (profitability, market share and customer satisfaction), and aimed at detecting the existence of differences of statistical significance in the responses of employees at Coca-Cola Company And the extent to which senior management is committed to strategic directives in order to achieve the highest return on investment and growth of market share and achieve customer satisfaction through knowledge of their current and future needs. The research community of the employees of the Coca-Cola Company for soft drinks, the branch of Babylon (365) workers, and the sample of the research was chosen by the method of class stratified, by (85) single, and the research was based on descriptive analytical method, The second part consisted of a questionnaire that was built and developed to measure the objectives of the research and hypothesis testing. It consisted of two parts which represent the first part of them in the types of strategic directions, while the second part included the dimensions of marketing performance. SPSS was used in data analysis using the statistical package program For The research found a number of results, the most important of which was the positive impact of the strategic orientation on marketing performance. The researcher also made many recommendations in the light of these results. Recommendations The adoption of the Coca-Cola Company for soft drinks Babylon Branch for both strategic guidance (proactive, defensive, creative) and those directives have a significant impact and clear on the marketing performance, which confirmed through the search results